Accounting faculty colloquium on ethics - Juan, Delilah; Mohamad, Shafi (Universiti Teknologi MARA, Sarawak, 2007)
The Accounting Faculty held a colloquium on the much-debated topic of ethics on March 2, 2007. Associate Professor Haji Shafi Mohamad presented his findings from a joint research, "A BiNational Study of Accounting Students' Ethical Attitudes", with Dr. Conor O'Leary of Queensland University of Technology, Australia. The paper had earlier been presented at the 17th Asia Pacific Accounting Conference on International Accounting Issues in Wellington, New Zealand on November 22, 2005. The paper compared the ethical attitudes of final year accounting students over a number of similar ethical scenarios across two jurisdictions Malaysia and Australia and has been published in the Malaysian Accounting Review a refereed accounting journal.